Reconstructing Feminism through Gender Roles, Women’s Opportunities, and Love in Greta Gerwig’s Little Women - Sarsono Sarsono; Ryana Dewi; Abdulloh Abdulloh; Slamet Basuki; Eny Suprihandani (STIBA IEC JAKARTA, 2026)
The purpose of this study is to analyze the feminism issues faced by women in the film Little Women (2019) directed by Greta Gerwig which is adapted from the classic novel by Louisa May Alcott. This study also examines the representation of feminism in Greta Gerwig’s Little Women focusing on gender roles and expectations, women’s opportunities and ambitions, and the institution of love and marriage as sites of inequality and restriction. Using a qualitative descriptive method, a feminist approach and textual analysis, selected scenes and dialogues are examined to reveal how gender roles shape women’s ambitions and how marriage functions not merely as a romantic resolution but as an economic and ideological institution. The findings indicate that Gerwig’s adaptation reconstructs feminism by presenting diverse forms of female agency rather than a singular feminist ideal such as a) gender roles and expectations, b) woman’s opportunities and ambitions, c) love and marriage. The study concluded that some problems arose in Little Woman such as inequality and restrictions experienced by female characters Jo, Amy, Meg, and Beth, and how they deal with these issues in their own ways. They are not only showing incredible determination, but they are also actively making progress toward freedom and equality in their lives. Based on the analysis, the researcher hopes this study inspires and broadens to appreciate regardless of gender, both men and women